Hedging in Jay Shetty’s Mental Health Podcast: A Pragmatic and Politeness Analysis - Nadia Mauliana; Zia Hisni Mubarak (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study investigates the pragmatic function of hedges in mental health conversations through a case study of Jay Shetty's interview with Kendall Jenner. Hedges, linguistic devices that convey uncertainty, politeness, or subjectivity, are commonly used in spoken discourse, especially when addressing personal or emotionally sensitive topics. Drawing on the theories of  Hyland (1996) and Brown et al. (1987), this research analyzes how hedging allows speakers to navigate vulnerability, protect face, and manage interpersonal dynamics in a highly public setting. The data were collected from a transcription of the podcast episode and analyzed qualitatively based on hedge types and their communicative roles. Findings show that Kendall Jenner uses hedges such as “I think,” “sometimes,” “kind of,” and “feel like” to soften the emotional weight of her statements, signal uncertainty, and maintain a relatable public image. Jay Shetty also employs hedging as a strategic tool to guide the conversation with empathy. This research contributes a novel perspective by applying pragmatic analysis to celebrity discourse in mental health advocacy, offering valuable insights into how language shapes public vulnerability and self-disclosure.